PERKECAMBAHAN DAN PERTUMBUHAN TANAMAN JAGUNG (Zea mays L) DENGAN APLIKASI PUPUK HAYATI PGPR - Hilwa Walida (UNIVERSITAS LABUHANBATU, 2019)
Efforts to increase corn production through intensification and extensification are always accompanied by the use of fertilizers. The use of chemical fertilizers in excess of the dose and carried out continuously can cause soil degradation. The aim of this research was to know the effect of PGPR application on germination and growth of maize crop (Zea mays L). This research was conducted with 2 treatments ie soaking the seeds with water (control) and soaking the seeds with PGPR biological fertilizer for 30 minutes. Each treatment consisted of 25 replicates each planted in a polybag. The parameters observed were germination, high velocity, number of leaves, and plant height. Sprout seed maize with PGPR application of 86%, high velocity two days, the average number of leaves in the eighth week after planting was 15 pieces, the average height of the plant in the eighth week after planting was 150 cm. Sprout seed maize on control of 70%, high velocity three days, the average number of leaves in the eighth week after planting was 8 pieces, the average height of the plant in the eighth week after planting was 100 cm. Based on the results known, the application of PGPR give the effects on germination and growth of maize. Keywords: Germination, Growth, Maize Plant, PGPR application